2004
DOI: 10.1002/cyto.a.20080
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol sensitivity of detergent resistance: A rapid flow cytometric test for detecting constitutive or induced raft association of membrane proteins

Abstract: Background: Lipid rafts are cholesterol-and glycosphingolipid-rich microdomains in the cellular plasma membranes that play critical roles in compartmentalization (concentration, coupling, and isolation) of receptors and signal molecules. Therefore, detecting constitutive or induced raft associations of such proteins is of central interest in cell biology. This has mostly been done with timeand cell-consuming immunobiochemical techniques affected by several sources of artifacts. A flow cytometric analysis of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…We and others have shown that some membrane-associated proteins can be resistant to Brij-58 detergent extraction under specific conditions (28,29,37,38). We evaluated the effects of Brij extraction on ERM protein distribution in freshly isolated CD4 T cells.…”
Section: Effect Of Age On the Distribution Of Molecules Between The Bmentioning
confidence: 99%
“…We and others have shown that some membrane-associated proteins can be resistant to Brij-58 detergent extraction under specific conditions (28,29,37,38). We evaluated the effects of Brij extraction on ERM protein distribution in freshly isolated CD4 T cells.…”
Section: Effect Of Age On the Distribution Of Molecules Between The Bmentioning
confidence: 99%
“…They are characterized by the enrichment of cholesterol, sphingolipids, and saturated phospholipids, and, in addition, by their insolubility in different detergents such as Triton X-100 and Lubrol WX (4). Rafts are thought to function as platforms for the dynamic association of signaling molecules.…”
mentioning
confidence: 99%
“…Mildly oxidative modification of LDL was achieved by dialyzing purified LDL fractions (1 mg protein/ml) against 5 lM CuSO 4 for 36 h, and afterwards, the Ox-LDL was sterile filtered. ), fixed in 4% paraformaldehyde for 15 min, quenched with 50 mM NH 4 Cl/glycin for 15 min, and then blocked with PBS/0.5% BSA for 15 min at RT. Afterwards, cells were incubated with anti-ceramide mAB 15B4 for 3 h at 4°C and then labeled with goat anti mouse-Cy5 (Abcam, Cambridge, United Kingdom) secondary antibody for 1 h at 4°C, followed by incubation with theta-toxin-FITC for 20 min at 4°C (KFB, Regensburg, Germany) for cholesterol staining.…”
mentioning
confidence: 99%
“…This raises the question, how the detergents influencing actin polymerization in vitro act on DRMs in intact cells. This approach is appealing, since recently, a flow cytometric method was developed for DRM isolation, called FCDR assay (29)(30)(31)(32)(33)(34). In these works, raft-associated proteins labeled by fluorescently tagged antibodies remained cell associated, after detergent solubilization of the whole cells.…”
Section: Original Articlementioning
confidence: 99%
“…Lipid rafts involved in cell signaling or membrane and protein trafficking are plasma membrane lipid heterogeneities containing elevated amounts of sphingolipids, cholesterol, GPI-anchored and other particular ''raft'' proteins (23)(24)(25)(26)(27)(28). The methodologically defined detergent-resistant membranes (DRMs), which considered to show comparable chemical properties to rafts, are identified applying the same TX100, Brij and CHAPS detergents and used in recently developed cytometric DRM measurements [flow cytometric detergent resistance (FCDR) assay] (29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%